DESAIN SISTEM INFORMASI PERSEDIAAN BARANG STUDY KASUS MAULANA BAKERY - Devita Maulina Putri; Mardiana Andarwati; Bony Laparsa (Jurnal Informatika, 2020)
Maulana bakery is a business entity engaged in making bread, cakes, tarts and various other snacks. The problem that occurs in this home industry is located in the current system for processing data in and out of goods, how to record it through a ledger, there is no data processing that uses a more effective database system, so that sometimes it has difficulty in calculation existing goods. The purpose of this study is to create a Goods Inventory Information System that can manage and manage incoming goods, exiting goods, stock items, ordering transactions using the Waterfall method by using a website for easier program operations. Whereas for structure modeling using Data Flow Diagrams (DFD). The end result of this Information System can manage data incoming goods, data goods out, stock of goods and ordering online.